Unveiling the central metal effects in thiophene-substituted metalloporphyrins electrodes for electrochemical energy sources: A first-principles study - Hiba A. Ali (20487275) (2025)
The growing demand for efficient energy storage solutions has highlighted the potential of organic electrode materials (OEMs) in metal ion batteries (MIBs). Metalloporphyrins, especially those decorated with thiophene at the meso positions, demonstrate significant potential due to their distinct electrochemical properties. This study employed the first-principles computational approach to explore how different central metals (Zn, Cu, Ni) affect the redox properties, thermodynamics, and performance of M(II)-porphyrins. Zn(II)-porphyrin exhibits a redox potential 0.62 V lower than Cu(II) and 0.71 V lower than Ni(II), making it suitable as a cathode material. Cu(II)-porphyrin, with its enhanced electron affinity, is more suited for anode applications. Periodic DFT calculations revealed key insights into their stability and interaction with PF6‾ anions, with complexation affecting the Fermi level and electronic properties. This work underscores the central metal's role in optimizing electrochemical performance, aiding in the development of eco-friendly energy storage systems. Other Information Published in: Journal of Power Sources License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.jpowsour.2025.236284